يثرب في شعر شعرائها - أحمد عدنان; يونس علي (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هذه الدراسة محاولة لتسليط الضوء على يثرب كما تجلت في شعر شعرائها, ويثرب كما هو معروف, كانت حاضرة من حواضر الحجاز في العصر الجاهلي, توفرت فيها كل مقومات الحياة بأشكالها الطبيعية والاقتصادية والاجتماعية, إضافة إلى كونها قد أنجبت مجموعة من الشعراء, كان لهم أثرهم في حركة الشعر الجاهلي, ثم كان لأكثرهم دور بارز في حركة الشعر في صدر الإسلام فيما بعد. وقد تبين أن أحاديث الشعراء اليثربيين عن مدينتهم قد تناولتها من خلال معطيات ثلاثة هي: الطبيعي والعمراني والاجتماعي, وقد جاءت المادة الشعرية متناسقة مع هذه المعطيات, فإذا بالمكان يتجلى وفقاً لرؤية الشاعر والحالة التي أراد التعبير عنها. This study tries to shed light on Yathreb as shown in the poetry of its poets. Yathreb was one of Alhijaz Urban Centers in the Pre-Islamic Age (Aljahili Age), in which all life constituents were present with their natural, economical and social forms. Moreover, it had a group of poets who influenced the movement of Aljahili Poetry. Most of those poets had a prominent role in the poetry movement of the early Islamic Age. It has been shown that the talks of Yathreb Poets about their city came through three trends: the natural, the urban and the social. The poetical material came in harmony with these trends; thus the place came up according to the vision of the poet and the situation he wanted to express.